Potential dosimetric benefits of four-dimensional radiation treatment planning. - Starkschall G; Britton K; McAleer MF; Jeter MD; Kaus MR; Bzdusek K; Mohan R; Cox JD; Starkschall, George; Britton, Keith; McAleer, Mary F; Jeter, Melenda D; et al. (International Journal of Radiation Oncology, Biology, Physics, 2009)
Purpose: To determine the extent of dosimetric differences between conventional three-dimensional (3D) dose calculations and four-dimensional (4D) dose calculations based on deformation of organ models. Methods and Materials: Four-dimensional dose calculations were retrospectively performed on computed tomography data sets for 15 patients with Stage III non-small-cell lung cancer, using a model-based deformable registration algorithm on a research version of a commercial radiation treatment planning system. Target volume coverage and doses to critical structures calculated using the 4D methodology were compared with those calculated using conventional 3D methodology. Results: For 11 of 15 patients, clinical target volume coverage was comparable in the 3D and 4D calculations, whereas for 7 of 15 patients, planning target volume coverage was comparable. For the other patients, the 4D calculation indicated a difference in target volume dose sufficiently great to warrant replanning. No correlations could be established between differences in 3D and 4D calculations and gross tumor volume size or extent of motion. Negligible differences were observed between 3D and 4D dose-volume relationships for normal anatomic structures. Conclusions: Use of 4D dose calculations, when possible, helps ensure that target volumes will not be underirradiated when respiratory motion may affect the dose distribution.